A anual of laboratory and diagnostic tests - Fischbach, Frances Talaska Dunning, Marshall Barnett (Wolters Kluwer Health, 2015)
Organizing content the way a nurse thinks-- by specimen and function-- the authors prepare students to deliver safe, effective, and informed care for patients undergoing diagnostic tests and procedures.